South Korea and the EU battling COVID-19: shared contribution to global health governance and human security - Tereza Novotná; Nam Kook Kim (Asia Europe Journal, 2023)
Commemorating the 60th anniversary of diplomatic ties, the article analyzes public health governance during the COVID-19 pandemic in the EU and South Korea. Shifting focus from traditional national security to a more people-centered understanding, the article employs the human security framework to examine nuances of the global health crisis. Through this theoretical lens, the research empirically compares and contrasts the EU's and South Korea's differing strategies battling COVID-19 from the pandemic's inception to the mass vaccination rollouts. While the EU's early approach was initially marked by slower responsiveness and border closures, South Korea stood out for its swift counter-epidemic measures, leveraging technological innovations and public–private partnerships. Yet once vaccination campaigns started, South Korea had to catch up with Europe. The article chronologically presents its findings, identifying a mutual convergence in approaches with the Omicron's emergence. In conclusion, the article distills seven key lessons from the pandemic management: the significance of independent public health institutions, the role of digitalization and transparency in fostering public trust, the shared responsibility to bridge the vaccination gap and invest in robust public health systems, and the paradigm shift towards human security combined with the resurgence of state which has to be balanced with safeguarding individual liberties and a collective global action. In addition, the article underscores potential avenues for a strengthened EU-South Korea collaboration to enhance global health governance beyond the confines of major geopolitical rivalries.
Keywords: 300